Comparative Study of Vibrational Spectra of Two Bioactive Natural Products Lupeol and Lupenone Using MM/QM Method. Issue 3 (3rd June 2012) - Dwivedi Dwivedi, Apoorva Apoorva; Pandey Pandey, Anoop Kumar Anoop Kumar; Raj Raj, Kanwal Kanwal; Misra Misra, Neeraj Neeraj
Abstract : This work deals with the theoretical study on the molecular structure and vibrational spectra of two well-known natural products: lupeol and lupenone. The spectra were interpreted with the aid of normal mode analysis following full-structure optimization carried out with the hybrid two-level ONIOM (B3LYP/6-31G: PM3) method. A detailed interpretation of the infrared spectra of Lupeol and Lupenone is also reported in the present work. The similarities and differences between the vibrational spectra of the two molecules studied have been highlighted. The scaled theoretical wave numbers are in perfect agreement with the experimental values. The thermodynamic calculations related to the title compounds were also performed at B3LYP/6-31G: PM3 level of theory. Quantum chemical calculations have been carried out to understand the dynamical behavior of the bioactive molecules Lupeol and Lupenone.